Spatial Variation in the Composition and Diversity of Fishes Inhabiting an Artificial Water Supply Lake, Eastern China - Guo, Chao; Li, Shiqi; Li, Wei; Liao, Chuansong; Zhang, Tanglin; Liu, Jiashou; Li, Lin; Sun, Jiaxin; Cai, Xingwei; Hansen, Adam G. (Frontiers in Ecology and Evolution, 2022)
With the intensification of eutrophication, many artificial water supply lakes that act as a biological filter for water diverted from rivers have been built to alleviate water scarcity in Eastern China. In this study, we selected Lake Yanlong, a representative artificial water supply lake in Yancheng City, as our experimental lake to explore how the community composition of fishes changed among different habitat types and assess potential consequences for effective water treatment. From October 2015 to October 2020, we conducted quarterly surveys of fish communities and environmental factors in the Mangshe River (MR; water for lake) compared to four different water treatment zones of Lake Yanlong (PZ: the pretreatment zone with inlet from the MR, EZ: the emergent macrophyte zone, SZ: the submerged macrophyte zone, DZ: the deep purification zone with outlet to urban waterworks). A total of 16,339 individual fish belonging to 11 families and 49 species were collected. Six of the eight dominant species observed across zones were small-bodied fishes. Despite reduced fish species richness, the relative abundance and biomass of fishes tended to be higher in Lake Yanlong relative to the MR. The Shannon-Wiener diversity index, Pielou evenness index, Simpson’s diversity index all decreased from the MR to the DZ in the following sequence: MR < PZ < EZ < SZ < DZ. Analysis of similarities and similarity percentage analysis confirmed that fish communities differed significantly among zones and Coilia ectenes, Carassius auratus, Pseudobrama simony, Hemiculter leucisculus, Hemiculter bleekeri were the major differentiating species. Mantel’s test and redundancy analysis revealed that water depth, aquatic vegetation coverage, and phytoplankton concentrations were the major factors determining the spatial distribution of fishes when moving from the MR to the DZ of Lake Yanlong. Stocking piscivorous fish can be used as an effective measure to control the abundance of prolific small-bodied fishes in Lake Yanlong. The details backing these findings are important for understanding how the community composition of fishes among habitat types in Lake Yanlong influence water quality, and to develop suitable biomanipulation strategies for the management of fish resources and maintaining proper function of these artificial water supply lakes.